Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Pada Materi Himpunan - Siti Laelatul Fitriyah; Haerudin Haerudin (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
Solving Mathematical issue is a crucial skill that students must acquire to solve mathematical problems. This study aimed to describe students' skills on solving mathematical issues on mathematic set. This study employed a descriptive qualitative design. The subjects of this study were 30 first-grade students of 1 Lebaksiu Junior High School during the 2020/2021 academic year who were selected using the purposive sampling technique. This research employed tests, interviews, and documentation to colled data. The instrument aimed to discover 2 item description questions regarding the problem-solving ability of the set material with indicators of mathematical problem solving based on Polya's theory, namely: 1) understanding the problem 2) planning the solution 3) solving the problem according to the plan 4) checking the procedure and the results of the solution. To analyze the data, data reduction, data presentation, and conclusion drawing was employed.